Room temperature positive magnetoresistance via charge trapping in polyaniline-iron oxide nanoparticle composites - Lin, Aigu L. (2013)
We demonstrate a polyaniline-iron oxide nanoparticle (PANI-NP) organic hybrid composite device with room temperature positive magnetoresistance of 85.7%. Temperature dependent resistivity measurements attribute this observation to the decrease in localization length of the charge carriers in the presence of an external magnetic field which result in them being trapped within the device between the insulating PANI layer, hence allowing the device to maintain its resistive state even when the power is switched off, thus exhibiting a memory effect.